Primary Lymphoepithelioma-Like Carcinoma of Lung - Alejandro Guerrero; Michael Laflamme; S Nicholas Agoff; William M Williams; Riyad Karmy-Jones (Canadian Respiratory Journal)
Primary lymphoepithelioma-like carcinoma (LELC) of the lung is a neoplasm seen most commonly in the nasopharynx of individuals from south China and Taiwan, and is strongly associated with the Epstein-Barr virus. The case of a 62-year-old Chinese man with a rare primary lung T2N1M0 LELC of the left lower lobe is presented. The lesion was further notable because of the presence of necrotizing granulomatous inflammation. The patient was treated with surgical resection. After it was determined that the neoplasm was of primary lung origin, adjunctive chemotherapy was initiated. The role of adjunctive chemotherapy in this setting is discussed.